Dihydropyridine Enhances the Antioxidant Capacities of Lactating Dairy Cows under Heat Stress Condition - Meng-Fei Yu; Xin-Mao Zhao; Hang Cai; Jian-Ming Yi; Guo-Hua Hua (Animals, 2020)
Heat stress (HS), a nonspecific response to environmental heat, can seriously affect dairy cow health. Feed additives may alleviate HS in dairy cows by improving rumen fermentation efficacy, stimulating feed consumption, enhancing vasodilation, and/or improving antioxidant capacity. The temperature–humidity index (THI) indicates that spring is a non-HS season, and summer is an HS season. HS results in the decrease in dairy cow antioxidant capacities. Our results indicated the decrease in superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT), and total antioxidation (T-AOC) levels and the increase in malondialdehyde (MDA) level during HS season. Meanwhile, antioxidant indexes (SOD, GSH-Px, and T-AOC) were positively correlated with milk yield (p < 0.01), whereas MDA exhibited a significant negative correlation with milk yield (p < 0.05). In addition, the effects of dihydropyridine (DHP) on antioxidant capacity and ruminal microbial communities in dairy cows under HS were investigated. During summer, dairy cows were randomly assigned into two groups under HS, including a standard diet (S-ND) group and standard diet with 3 g/day/cow DHP (S-D) group. DHP treatment significantly restored SOD and GSH-Px levels under HS. Denaturing gradient gel electrophoresis results indicated that the DHP altered ruminal bacterial community mainly composed Proteobacteria and Firmicutes in dairy cows under HS. Our results suggest that DHP can enhance the antioxidant abilities of dairy cows with favorable effects on ruminal microbial communities under HS, further alleviating HS on dairy cows.